PENERAPAN EXPRESSING WRITING DALAM MENINGKATKAN ADVERSITY QUOTIENT PADA ANAK PANTI ASUHAN - Inayah Nabila Abdjul; Adinda Kartika Putri Neoe; Anisa Anisa; Fajriah An. Sabbu; Fatra Adjis; Marya Danisyah Mandagi; Maya Maya; Anik Indarwati (program studi psikologi, 2023)
This study was conducted to determine whether there was an increase in adversity quotient after implementing expressing writing in orphanage children. This research method uses a quantitative research type and uses a pre-experimental design experiment with a pretest-posttest one group design research type. This type of user is imposed on one group only without a comparison group with a total of 30 populations and 14 samples, The results of this study are that the subjects did a pretest with a total value of 104.36 then given treatment and after being given treatment the subjects did a posttest with a total value of 111.29. which means that the subject's AQ increased by 6.7% with a significance of 0.001 <0.05 which means significant.